Business Resiliency of Travel Agencies in the Volatile, Uncertain, Complex, and Ambiguous (V.U.C.A) World - Jannyle M. Olano, Jannyle M. Olano (JPAIR Multidisciplinary Research, 2022)
Today, we live in a VUCA world, which stands for Volatility, Uncertainty, Complexity, and Ambiguity, raised to the third power. That is because of current changes in the world, such as social, business, financial and economic, technological, cultural, and educational changes. The purpose of this research is to attempt to develop a concept for organizational resilience in the face of economic change for travel agencies in the 2nd district of Albay. The study used a mixed-method research design to determine the perceptions of both owners and their employees, while five-point indicators were provided in the different areas to determine the respondents' business resiliency practices with the aid of the Likert scale. The analyzed data of the travel agency believed “slightly agree” on the business resiliency when the practice is exceedingly observed and predominantly exercised along with the services delivery platform (4.61), sales and marketing (4.21), human resource (4.23), financial management (4.32), and safety and security (4.69). Furthermore, all the above-mentioned variables were tabulated t at 1% and had a value of 10.48. Therefore, it is proposed that there are still necessary actions and resolutions to be made in order to be ready to further enhance the business resiliency of the VUCA World under this study. In this light, more effective management skills and strategies are required in order to address the identified challenges of the respondents. The travel agency owners must have a strategic model that will guide them in achieving their goals and sustaining their business.
Keywords: tourism; business resiliency; practices; mixed method design; VUCA World; travel agency; Philippines